TINJAUAN HUKUM PENGURUSAN IZIN PENDIRIAN PERSEROAN TERBATAS OLEH NOTARIS - Devi Anggriyani Purwanti (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Many enteurprenuers choose to set up companies in the form of PT to conduct their business activities. And to make the PT legal as a legal entity there are conditions and procedures that must be met. The establishment of PT can not be separated from the role of the notary to make the legality of the permit to establish PT. This made notary have legal responsibility for the establishment permit of PT. So the problem is fomulated in this thesis was how the terms and procedures for obtaining a license for establishing a limited company by notary and how the notary’s legal resposibility for the management of the establishment of limited company.From the results of the thesis, it was fond that the conditions for establishing a PT were in accordance with law number 40 of 2007 concerning limited liability companies, namely the excistence of a deed containing the articles of associaton and all elements contained in the company law. The making of a deed for the PT establishment permit must be by a notary where the founders met the notary, who than checks the name, the signing of the registration deed to the ministry so that the legal entity decrees are released. By the goverment at this time the process can be done online through the OSS program, so that the registration process to the ministry becomes easier.What needs to be done by the founder is only to prepare the certificate of establishment of the PT by the notary and then go to the lams oss.go.id and follow the instruction on the page.As for the responsibility of the notary in the management of PT establishment permit, the deed of establishment of the PT was made. The responsibility in question is the responsibility for the validity of the proof of deed and related to the making of the deed of establishment of PT which must be in accordance with the provisions stated in the laws and regulations. However, the notary also has the right to obtained legal protection against the deed that they made. This protection takes the form of a notary honor council. As a body that decides whether the notary concerned can be declared violating a notary code of ethics and has the right to be investigated by investigators from both the police and the prosecutor’s office.